Estimasi Area Tergenang Akibat Kenaikan Muka Air Laut Menggunakan Data Unmanned Aerial Vehicles (UAV) pada Kawasan Pesisir Teluk Ambon Dalam, Provinsi Maluku, Indonesia (Studi Kasus: Kawasan Pesisir Desa Waiheru) - Noya, Theo Imanuel; Gaol, Jonson Lumban; Agus, Syamsul Bahri (Universitas Diponegoro, 2024)
The estimation model of potential tidal flooding areas in this study was built using altimetry satellite data for the period January 1993–July 2023, tidal data of Teluk Ambon Dalam (TAD) for the period 2012–2018, and Digital Terrain Model (DTM) data or land surface height recorded by the Unmanned Aerial Vehicle (UAV) DJI Mavic 2 Pro series. Satellite altimetry and tidal data were used to calculate the estimated values of the tidal flood inundation height in 2023 and 2050 under the highest tide conditions. UAV data recording was carried out at two variations of flight height, namely 80 m and 100 m, to determine the accuracy of the best geometry to be used in modeling. The bathtub-method approach was used to model the potentially inundated area by integrating the estimated inundation heights and DTM values. The results of the analysis of altimetry satellite data for the period 1993–2023 showed that the value of the sea level rise rate of Ambon Bay waters is 4 mm/year. The estimated value of tidal flood inundation extent in 2050 is 1.40 m. The flying height of 100 produces better geometry accuracy with a horizontal accuracy value of 1.51 m and vertical accuracy of 0.61 m at a scale of 1:5.000. Land elevation contours in the study area based on DTM data ranged from 0.12 - 1.82 m. Modeling results estimated that the inundated area in the study area in 2023 was 0.46 m and increased to 0.50 ha in 2050 due to sea level rise. Model estimasi area berpotensi tergenang banjir rob pada penelitian ini dibangun dengan menggunakan data satelit altimetri periode Januari 1993 – Juli 2023, data pasang-surut Teluk Ambon Dalam periode tahun 2012 - 2018 dan data Digital Terrain Model (DTM) atau ketinggian permukaan tanah hasil perekaman Unmanned Aerial Vehicle (UAV) seri DJI Mavic 2 Pro. Data satelit altimetri dan data pasut digunakan untuk menghitung nilai estimasi tinggi genangan banjir rob pada tahun 2023 dan 2050 saat kondisi pasang tertinggi. Perekaman data UAV dilakukan pada 2 variasi ketinggian terbang yakni 80 m dan 100 m untuk menentukan ketelitian geometri terbaik yang akan digunakan pada pemodelan. Pendekatan bathtub-method digunakan untuk memodelkan area berpotensi tergenang, yakni dengan mengintegrasikan nilai estimasi tinggi genangan dan nilai DTM. Hasil analisis data satelit altimetri periode tahun 1993 - 2023 memperoleh nilai laju kenaikan muka air laut perairan Teluk Ambon adalah 4 mm/tahun. Nilai estimasi jangkauan genangan banjir rob pada tahun 2050 adalah 1,40 m. Ketinggian terbang 100 menghasilkan ketelitian geometri yang lebih baik dengan nilai ketelitian horizontal adalah 1,51 m dan vertikal adalah 0,61 m pada skala 1:5.000. Kontur ketinggian tanah pada kawasan penelitian berdasarkan data DTM berkisar antara 0,12 – 1,82 m. Hasil pemodelan estimasi area tergenang pada kawasan penelitian tahun 2023 adalah seluas 0,46 m dan bertambah menjadi 0,50 ha pada tahun 2050 akibat kenaikan muka laut.